Sosialisasi Modul Edukasi Suami Siaga (ESS) tentang Pencegahan Stunting pada Suami Ibu Hamil Primigravida - Marsia Marsia; Erni Juniartati; Dwi Sulistyawati (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Stunting or short stature is a major health problem in Indonesia. Stunting can cause cognitive development disorders in toddlers. Standby husband education (ESS) is one of the educational solutions offered to prevent stunting in babies carried by mothers during pregnancy. This community service aims to increase knowledge and develop attitudes in the working area of ​​the North Singkawang Health Center 1. The sample in this study was 40 Respondents of husband of a primigravida pregnant woman undergoing treatment at the Singkawang Utara I Public Health Center. This Community Service was carried out within a span of 10 months from the preparation of proposals, permits, field surveys, interventions, data analysis to the collection of reports. The implementation of community service is evaluated based on the level of knowledge and attitude in efforts to prevent stunting using a knowledge and attitude questionnaire. The results of the knowledge level of the respondents after being given socialization as big 65% with a good level of knowledge and 35% with a fairly good level of knowledge. The attitude of the respondents after being given socialization as big 100% with a positive attitude category. The expected results of this community service are as a reference for programs at the Public Health Center  / Health Office in an effort to prevent stunting.